Electrodeposition of Twinned Cu with Strong Texture Effect on Voiding Propensity in Electroplated Cu Solder Joints. Issue 16 (4th January 2021) - Chiang, Ping-Chen; Shen, Yu-An; Feng, Shien-Ping; Chen, Chih-Ming
Abstract : Electrodeposition of Cu receives considerable attention due to its wide application in microelectronic products. Sn-rich alloys are commonly used to join the electroplated Cu to form solder joints, while their interactions give rise to undesired Kirkendall voids. Suppression of voids is imperative to ensure reliable solder joints with mechanical robustness. In this study, twinned Cu with various crystal orientations are constructed using electroplating and their efficacy on void suppression are investigated. Four Cu electroplated films (Cu A, B, C, and D) with numerous twin boundaries and different (111) and (110) ratios are joined with Sn-rich solder (SAC305) and thermally aged at 200 °C. The voiding propensity is in an order of Cu D > Cu C > Cu B > Cu A, inversely corresponding to their (111) ratios (Cu A > Cu B > Cu C > Cu D). Particularly, a void-free solder joint constructed by the electroplated Cu A film with plenty of twinned bamboo structures is observed. The findings demonstrate that Σ3 twin boundary in the bamboo structure with ⟨111⟩-preferred orientation has much higher efficiency at suppressing the Kirkendall effect than that in ⟨110⟩-preferred Cu films.